SISTEM INFORMASI PERPUSTAKAAN SEKOLAH BERBASIS WEBSITE DI SMP ISLAM MENTARI INDONESIA KABUPATEN BEKASI - Baroroh, Niswatun; Rustiana, Rahmat; Hermalia, Tita; Hermawan, Yadi (Program Studi Manajemen Pendidikan Islam, 2023)
Libraries are the main supporting facilities for education, be it primary, secondary or higher education. The main purpose of the library is to provide facilities that can improve the quality of learning where students and educators can add insights easily through various books and other references provided. Book circulation arrangements in the library have a very important role in improving the effectiveness of library management, especially those related to the process of borrowing and returning books borrowed by participants. However, Mentari Indonesia Islamic Junior High School does not have these supporting facilities, so participants cannot find out what collections are in the library. In addition, the process of borrowing and returning books by members is not recorded properly because it still relies on manual recording with paper that is prone to loss or damage. Therefore, a technology is needed that can make it easier for students and teachers to find books, manage the process of borrowing and returning books and keep the data from these activities from being easily lost. To realise this, a website-based library information system needs to be designed and created. The method used in website development is the waterfall method which is one of the popular methods in software development. The result of this design is a website application that is able to support library administration work while being able to handle existing problems. As an effort to evaluate the results of the design, the website was tested using the black box method to show that functionally the application can run well. The test results show that all the features designed can run well and without causing errors.